Pengaruh Kompensasi dan Kompetensi terhadap Kinerja Karyawan pada PT. Bara Putra Pratama - Handayani, Risma; Haryoto, Cecep Yoto (Jurnal EMT KITA, 2025)
This study aims to examine and analyze the influence of Compensation and Competence on Employee Performance at PT. Bara Putra Pratama. The independent variables used are Compensation and Competence, while the dependent variable is Employee Performance. Data collection in this study was conducted by distributing questionnaires to 50 respondents from PT. Bara Putra Pratama employees. The research method used was an associative quantitative method using primary data and data processing using Statistical Software for the Social Sciences (SPSS). The results of this study indicate that Compensation has a positive and significant effect on Employee Performance with a calculated t value greater than t table (6.396 > 2.014) and a significant value of 0.001 < 0.05. Competence has a positive and significant effect on Employee Performance with a calculated t value greater than t table (7.733 > 2.014) and a significant value of 0.001 < 0.05. Together, Compensation and Competence have a significant effect on Employee Performance with a calculated F value greater than F table (65.843 > 3.20) and a significant value of 0.001 < 0.05.
Keywords: Compensation; Competence; Employee Performance